2018
DOI: 10.4103/jisp.jisp_254_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of clarithromycin as an adjunct to scaling and root planing: A randomized clinical trial

Abstract: Background:Administration of systemic antibiotics may implement persuasive treatment effect for chronic periodontitis by intending tissue-invasive bacteria in addition to accustomed nonsurgical periodontal therapy (NSPT).Aims:The aim of this study was to assess the ancillary effects of oral clarithromycin (CLM) along with NSPT for chronic periodontitis.Materials and Methods:Thirty periodontitis patients were randomly divided into two equal groups in this double-blind, randomized, parallel group, and active-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 34 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…A total of 18 756 citations were found during the electronic and manual search; after reviewing title and abstract, 451 studies were considered as relevant and were further screened ( κ = 0.84). Of these, 106 papers were evaluated for the full‐text examination ( κ = 0.91): Finally, 85 studies were excluded ( κ = 0.98), since they did not satisfy the eligibility criteria (Table ), and the remaining 21 28‐48 studies were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 756 citations were found during the electronic and manual search; after reviewing title and abstract, 451 studies were considered as relevant and were further screened ( κ = 0.84). Of these, 106 papers were evaluated for the full‐text examination ( κ = 0.91): Finally, 85 studies were excluded ( κ = 0.98), since they did not satisfy the eligibility criteria (Table ), and the remaining 21 28‐48 studies were included in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The population consisted of 1344 subjects, with an age range of 32‐66 years. Smoking was considered as an exclusion criterion in nine studies, 28,29,31,32,37,38,42,44,47 while in one paper 43 no information was reported; smoking habit was defined in three 30,36,40 out of the eleven studies that reported the inclusion of smokers. Nine different antimicrobials with a wide range of dosage and duration were analyzed in the included trials; in addition, discrepancies in the SRP approach were also retrieved, since twelve RCTs 28,29,32,33,35,36,38‐41,46,48 performed a staged mechanical treatment, while four RCTs 30,31,34,35 adopted a full‐mouth approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials comprised 524 participants. Studies included a minimum of 30 [15] up to 180 [10] subjects.…”
Section: Characteristics Of the Includedmentioning
confidence: 99%
“…e target population included generalized aggressive periodontitis (GAgP) in two studies [13,16], chronic periodontitis (CP) in three studies [12,14,15], and moderate-to-severe periodontitis in two studies [10,11]. e subgingival debridement regime ranged from a full-mouth approach in one session [13,16] to a staged approach over 14 days [11,12,14].…”
Section: Characteristics Of the Includedmentioning
confidence: 99%